Myocarditis Mimicking STEMI Complicated by Complete Atrioventricular Block: Diagnostic and Therapeutic Insights - Rido Mulawarman; Hiradipta Ardining; Celly Anantaria Atmadikoesoemah; Dony Yugo Hermanto; Bambang Widyantoro; Rarsari Soerarso (Jurnal Kardiologi Indonesia, 2026)
Background: Myocarditis, or myocardial inflammation, may share similar characteristics to Acute Coronary Syndrome (ACS), particularly ST-Elevation Myocardial Infarction (STEMI). This condition is further augmented when a Complete Atrioventricular Block (CAVB) is present. Despite being rare, this condition may pose additional diagnostic and therapeutic challenges. Case Illustration: We report a 54-year-old woman with fatigue, dyspnea, fever, nausea, and watery diarrhea for three days. Upon admission, she experienced hypotension, pulmonary congestion, and a complete Atrioventricular (AV) block, with ST-segment elevation seen on the lateral leads. Initial laboratory results revealed markedly elevated high-sensitivity troponin T and C-reactive Protein (CRP). Bedside echocardiography showed a prominently reduced Ejection Fraction (EF) (40%) alongside the presence of regional wall motion abnormalities. Urgent coronary angiography revealed only non-obstructive coronary disease and no obstructive coronary disease. A temporary pacemaker and inotropic support were initiated. Given the presence of systemic prodromal symptoms and the absence of coronary obstruction, myocarditis was strongly suspected. High‑dose intravenous methylprednisolone was given as an anti‑inflammatory treatment in suspected fulminant myocarditis with cardiogenic shock and complete AV block. Recognizing that immunosuppressive therapy is not routinely recommended for all myocarditis cases, especially without biopsy confirmation. Cardiac magnetic resonance imaging subsequently confirmed myocarditis, demonstrating myocardial edema and subepicardial late gadolinium enhancement. The patient was discharged after receiving guideline-directed medical therapy and tapering corticosteroids, with preserved ventricular function on follow-up 1 month after discharge. Conclusions: This report illustrates the importance of a stepwise diagnostic approach to differentiate myocarditis from STEMI, particularly when complicated by conduction disturbances such as CAVB. Early recognition and timely initiation of immunosuppressive therapy can lead to favorable outcomes.